Evolutionary effects of geographic and climatic isolation between Rhododendron tsusiophyllum populations on the Izu Islands and mainland Honshu of Japan - Yoichi, Watanabe (Heredity (Edinb), 2021)
Geographic and environmental isolations of islands and the mainland offer excellent opportunity to investigate colonization and survival dynamics of island populations. We inferred and compared evolutionary processes and the demographic history of Rhododendron tsusiophyllum, in the Izu Islands and the much larger island Honshu, treated here as the mainland, using thousands of nuclear SNPs obtained by ddRAD-seq from eight populations of R. tsusiophyllum and three populations of R. tschonoskii as an outgroup. Phylogenetic relationships and their habitats suggest that R. tsusiophyllum had evolved and migrated from cold north to warm south regions. We detected clear genetic divergence among populations in three regions of Honshu and the Izu Islands, suggesting restricted migration between them due to isolated habitats on mountains even in the mainland. The three regions have different changes in effective population size, especially, genetic diversity and population size of the Izu Islands are small compared to the others. Further, habitats of populations in the Izu Islands are warmer than those in Honshu, suggesting that they have undergone adaptive evolution. Our study provides evidences of montane rather than insular isolation on genetic divergence, survival of populations and significance of adaptive evolution for island populations with small population size and low genetic diversity, despite close proximity to mainland populations.